ALGORITHM FOR SUBOPTIMAL DISTRIBUTION OF THE SOFTWARE COMPONENTS IN DISTRIBUTED SYSTEMS FOR TELECOMMUNICATIONS CONTROL - Valery P. Mochalov; Natalya Yu. Bratchenko (Вестник Северо-Кавказского федерального университета)
The item reveals a newly developed and implemented recurrent algorithm for optimizing the interaction among processor modules in distributed control systems.